The Role of Kolkisin in Multiplication of Planlet Banana Kepok Abu Poliploidi in Vitro - Sartika, Dewi; Agustrina, Rochmah; Ernawiati, Eti; Irawan, Bambang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Bananas are one of the horticultural crops of the fruit group that have quite high social and economic value. One type of banana that is very popular is the pisang kepok. The main obstacle in pisang kepok production is the availability of seedlings. The above constraints can be overcome by propagation of banana seedlings using tissue culture techniques by adding colchicine to the tissue culture media. Colchicine is often used to improve plant quality. This study aims to determine the effect of adding colchicine to the media on the growth and formation of pisang kepok abu plantlet. The study was conducted from November 2019 - February 2020 at the MTC Laboratory, PT Great Giant Pineapple PG 4, East Lampung. The concentration of colchicine added to the media was 0.1%. The growth and development of plantlets produced from media with colchicine treatment will be compared with plantlets from the control group. The tests were repeated 10 times. The results showed that the growth and formation of pisang kepok abu plantlets from the treatment of colchicine were lower than the growth and formation of the pisang kepok plantlets in the control group.